Studies on the formation of silicon nitride and silicon carbide from rice husk - Kuskonmaz, N; Sayginer, A; Toy, C; Acma, E; Addemir, O; Tekin, A (FREUND PUBLISHING HOUSE, 1996)
Rice husk is a potentially useful source material for the production of silicon nitride, silicon carbide or a mixture of both. Pyrolysis of rice husk yields an intimate and homogeneous mixture of carbon and silica which is highly desirable for a good carbonitrothermic or carbothermic reduction process. The formation of Si3N4 occurs on heating the pyrolysed rice husk to 1400 degrees C under nitrogen flow and SiC forms in the presence of excess carbon at temperatures above 1450 degrees C. SEM and XRD results show that the morphology of the nitride product is influenced by the reaction temperature and the presence of additives.
Keywords: COMPOSITES; Materials Science